Study of health seeking behavior and its determinants among attendees of urban health center, Dharavi, Mumbai, India - Patil, Subita P.; Parbhankar, Satish S.; Bansode-Gokhe, Seema S.; Shelke, Pallavi S.; Singh, Rakesh Darbar (International Journal Of Community Medicine And Public Health, 2016)
Background: Health seeking behaviour is an important factor in health management becomes relevant among under-privileged populations like urban slums, tribal populations. The objective of the study was to find out health seeking behavior and its determinants among attendees at Urban Health Center Dharavi, Mumbai. Methods: This cross sectional study was conducted among 400 attendees of General OPD at Urban Health Center, Dharavi, Mumbai by systematic random sampling from Jan. to Aug. 2015. The predesigned, pretested semi structured questionnaire was administered among them after their valid informed consent. Results: The mean age was 36.44(+/-14.10 SD) years, >3/4th were married, Muslims were dominating and belonged to socio economic class III and IV. Though they may have to purchase medicines from outsides almost all had trust in government health facility hence visiting this center. According to their perceptions about their own health, only 34% thought of healthy currently. More than 3/4th preferred government hospital in case of major illness while during minor illness home remedies due to trust in the health care services offered by them. Conclusions: It is essential to carry out health awareness measures so as to reduce acute respiratory tract illness in that area and reduce time gap between symptom and health care services availed.